Optimization of Biodiesel Development from Non-Edible Indigenous Feedstocks in Nigeria - Amadi, Nwoko, Christopher Ikpe; Udoka, Nkwoada Amarachi; Ugochi, Ogu Helen (The International Journal of Biotechnology, 2019)
This study investigated the transesterification of Rubber seeds (Hevea brasiliensis), Avocado Pear seeds (Gratissima persea), and Nipa Palm Kennel seeds (Nypa frutican) locally sourced from Nigeria as an adsorbate for the esterification reaction of oleic acid with methanol. Reaction was catalysed by potassium hydroxide (KOH) to form methoxide oleate (biodiesel) adsorption from aqueous solution in batch model for the production of biodiesel. The results obtained showed that rubber seeds oil (RSO), Avocado pear seeds oil (APO) and Nipa palm kernel seed oil (NPKO) oil gave maximum biodiesel yields at 0.9 % w/v, 0.1 % w/v and 0.1 % w/v catalyst concentration respectively. Their biodiesel yields were 88.0 %, 92.0 % and 96.7% respectively. They recovered biodiesel were characterized as an alternative fuel via specific gravity, viscosity, acid value, flash point and cloud point. The results obtained showed that the specific gravity for RSO (0.886 kg/m3), APO (0.876 kg/m3) and NPKO (0.850 kg/m3) were fairly significant at temperature of 25 oC to other conventional petroleum diesel ASTM D 975, standard biodiesel ASTM D975, and standard biodiesel ASTM 6751 and EN14214.